Ирония в поэзии Владлена Гаврильчика - Osiewicz, Bartosz (Studia Rossica Posnaniensia, 2020)
This article is devoted to the analysis of irony in Vladlen Gavrilchik’s lyrics, which belong to two directions in modern Russian poetry – “neo-primitive”, and “ironic, caricature-grotesque poetry”. Irony is one of the main literary techniques used by the Russian primitive poet. In the speech of Gavrilchik’s characters there is a hidden living author’s word, saturated with a hidden meaning. The recipient’s ignorance of the irony will certainly lead to interpretative failures. Therefore, Gavrilchik the ironist addresses his poetry to a reader who understands his poetic jokes and ironic games. The article also shows that Gavrilchik depicts Soviet reality in an ironic manner; he ironically reinterprets also socialist-realist images, simultaneously mocking the founders of socialist-realist poetics.